2016
DOI: 10.6002/ect.2014.0294
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Parathyroid allotransplant is a valuable alternative in treating permanent hypoparathyroidism. However, it is a difficult process that requires several trained staff and advanced laboratory equipment, which makes the costs high. Here, we identify a new parathyroid allotransplant technique. Materials and Methods: After obtaining informed consent from patients, parathyroid cell suspensions obtained from 4 donors who had undergone a subtotal parathyroidectomy owing to chronic renal failure were transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Allograft function was observed in 7 patients (70%) at a mean follow-up of 12 months. Daily oral calcium and vitamin D supplementations discontinued totally in 7 patients and no complications were observed [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Allograft function was observed in 7 patients (70%) at a mean follow-up of 12 months. Daily oral calcium and vitamin D supplementations discontinued totally in 7 patients and no complications were observed [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…As immunosuppressive therapy, prednisolone was administered from five days to 1 month (depending on the study) and then stopped. In both of their studies, Aysan and colleagues [67,68] reported no side effects and a success rate of 70% at a mean follow-up of 12 months.…”
Section: Allotransplantation Of Parathyroid Glandsmentioning
confidence: 95%
“…It was discovered that the biggest part of the parathyroid tissue presents the Human Leucocyte Antigen (HLA) class I only slightly expressed, so parathyroid cells may not be involved in transplant rejection. It has been possible to develop a long-running allograft that excludes the cells that express HLA class II antigens (i.e., lymphocytes, macrophages and granulocytes) from the insertion into the recipient [22,32,67,68].…”
Section: Allotransplantation Of Parathyroid Glandsmentioning
confidence: 99%
See 2 more Smart Citations